School-Based Surveillance of Respiratory Pathogens on “High-Touch” Surfaces - Murray, Alastair F.; Emanuels, Anne; Wolf, Caitlin; Franko, Nicholas; Starita, Lea; Englund, Janet A.; Chu, Helen Y. (Frontiers in Pediatrics, 2021)
In order to assess the presence of respiratory pathogens on “high-touch” surfaces and inform sanitation practices at schools, pre-selected surfaces in elementary schools in Seattle, WA, USA were sampled weekly and tested by RT-PCR for 25 viral respiratory pathogens (including SARS-CoV-2 retrospectively) and S. pneumoniae during 2019–2020 winter respiratory illness season. Viral pathogens (rhinovirus, adenovirus, influenza) known to cause respiratory illness were detected on commonly touched surfaces, especially wooden surfaces, and matched the patterns of circulating virus in the community.